Note on the Measurement of Elasticity of Substitution in International Trade - J. J. Polak (The review of economics and statistics, 2023)
The elasticity of export supply, as can be seen, is an increasing function of each of three variables: the elasticity of supply of the ex ported goods, the proportion of potential ex ports consumed domestically, and the elasticity